Perwari dalam Kemelut Revolusi Indonesia - Sasi, Galuh Ambar (Masyarakat Sejarawan Indonesia, 2021)
Women's movement during the Indonesian revolution focused on women mobilization in the Red Cross, paramilitary, liaisons, soup kitchens, organizational changes, and congresses. Reviewing Harry E. Poeze's writings regarding the relationship between the Persatuan Perjuangan and Persatuan Wanita Republik Indonesia (Perwari), this paper argues that the independence proclamation of Indonesia gave a new identity and transformation. These two processes gave birth to different imaginations and interpretations of Indonesianness, independence, the Indonesian revolution, and the position of women in the process. On the other hand, the difference in the imagination and meaning destroys Perwari and affects her movement patterns afterward. Finally, the experience of Perwari may be offering material discussion about an alternative discourse on the periodization of the Indonesian women's movement.